(untitled) (Olhar de Professor, 2023)
This article is based on a critical analysis to reflect on the meaning attributed to Pedagogy in the National Curriculum Guidelines for the Undergraduate Course in Pedagogy (2006) and in Resolution 02/2019 of the CNE that establishes the National Common Base for Initial Teacher Training of Basic Education (DCN-BNC). The methodology employed used as a corpus of analysis the official documents that guide Pedagogy courses in the country, Resolution CNE/CP 01/2006 and Resolution CNE/CP nº 2/2019. Historically, Pedagogy as an epistemological field has not found a place in the official documents that guide the training of pedagogues in the country, thus, the logic of Pedagogy is becoming natural in Brazil only as a degree course, separated from its epistemological dimension.